Serum Neurofilament Levels and PML Risk in Patients With Multiple Sclerosis Treated With Natalizumab. Issue 4 (July 2021) - Fissolo, Nicolás; Pignolet, Beatrice; Rio, Jordi; Vermersch, Patrick; Ruet, Aurélie; deSèze, Jerome; Labauge, Pierre; Vukusic, Sandra; Papeix, Caroline; Martinez-Almoyna, Laurent; Tourbah, Ayman; Clavelou, Pierre; et al.
Abstract : Objectives: The study aimed to assess the potential for serum neurofilament light chain (NFL) levels to predict the risk of progressive multifocal leukoencephalopathy (PML) in natalizumab (NTZ)-treated patients with multiple sclerosis (MS) and to discriminate PML from MS relapses. Methods: NFL levels were measured with single molecule array (Simoa) in 4 cohorts: (1) a prospective cohort of patients with MS who developed PML under NTZ therapy (pre-PML) and non-PML NTZ-treated patients (NTZ-ctr); (2) a cohort of patients whose blood was collected during PML; (3) an independent cohort of non-PML NTZ-treated patients with serum NFL determinations at 2 years (replication cohort); and (4) a cohort of patients whose blood was collected during exacerbations. Results: Serum NFL levels were significantly increased after 2 years of NTZ treatment in pre-PML patients compared with NTZ-ctr. The prognostic performance of serum NFL levels to predict PML development at 2 years was similar in the NTZ-ctr group and replication cohort. Serum NFL levels also distinguished PML from MS relapses and were 8-fold higher during PML compared with relapses. Conclusions: These results support the use of serum NFL levels in clinical practice to identify patients with relapsing-remitting MS at higher PML risk and to differentiate PML from clinical relapses in NTZ-treated patients. Classification of Evidence: This study provides Class I evidence that serum NFL levels can identify NTZ-treated patients with MS who will develop PML with a sensitivity of 67% and specificity of 80%.